Meeting goals of sustainability policy: CO2 emission reduction, cost-effectiveness and societal acceptance. An analysis of the proposal to phase-out coal in the Netherlands. (March 2020) - Akerboom, Sanne; Botzen, Wouter; Buijze, Anoeska; Michels, Ank; van Rijswick, Marleen
Abstract: The mitigation of global climate change renders effective policy indispensable. In this paper we evaluate a policy drafted in the Netherlands to close all its remaining coal-fired plants by 2030, which is well before the end of their technical and economic life spans. This plan is part of a package to reduce CO2 emissions with 25% by 2020 and 49% by 2030 in comparison to 1990. Under Dutch policy, all measures taken must meet three goals: CO2 emission reduction, cost-effectiveness and societal support. We will show that existing EU legal frameworks limit the effectiveness of the closure, because they allow for carbon leakage and lack a coordinated European strategy on the coal phase out, even though several EU member states have formulated similar plans. There is also no definitive answer as to whether the coal phase out is cost-effective. Dutch government will have to decide what the parameters of 'cost-effective' are. So far, the plan enjoys societal support. It is up to the Dutch government to decide what balance between CO2 emissions, costs and societal support is best. For further action, we recommend an EU strategy on the coal-phase out, in order to coordinate and to prevent carbon leakages. Highlights: This article presents a first in depth review of Dutch coal phase-out. We show that research on the actual contribution to CO2 reduction is inconclusive. Costs of a coal phase-out are difficult to calculate. We show societal acceptance is high, but could diminish in case of higher costs. We recommend coordinated EU policy with EU ETS measures.